The effects of glucocorticoid treatment on cardiovascular system in patients with systemic lupus erythematosus - Dominika Blachut,; Brygida Przywara-Chowaniec,; Jan Harpula,; Andrzej Tomasik,; Ewa Nowalany-Kozielska,; Beata Morawiec, (Archives of Rheumatology, 2022)
Objectives: This study aims to assess variables concerning arterial stiffness including carotid-femoral pulse wave velocity, carotid-radial pulse wave velocity, ankle-brachial index, and the advancement of atherosclerosis development. Patients and methods: Between October 2016 and December 2020, a total of 43 consecutive patients with systemic lupus erythematosus (SLE) (4 males, 39 females; mean age: 57±8 years; range, 42 to 65 years) were prospectively included in the study. All data were compared between the group treated with glucocorticoids and that not treated with these agents. Results: The study group consisted of 43 patients with SLE, while 22 (51%) patients were treated with glucocorticoids. The mean duration of SLE was 12.3±5.3 years. Patients treated with glucocorticoids had lower values of ankle-brachial index compared to those who were not treated with glucocorticoids (p=0.041), although the values were within the range. A similar situation was reported for the carotid-femoral artery pulse wave velocity (p=0.032). However, carotid-radial artery pulse wave velocity was not significantly different between both groups (p=0.12). Conclusion: Properly selected therapy is important in the prevention of CVD.